2022
DOI: 10.3389/fpsyt.2022.996451
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in anxiety and depression prevalence and their association with adverse outcomes in patients hospitalized for acute exacerbations of chronic obstructive pulmonary disease in Beijing, China, from 2004 to 2020

Abstract: AimsTo investigate the temporal trend in anxiety and/or depression prevalence in patients hospitalized for acute exacerbation of chronic obstructive pulmonary disease (AECOPD) in Beijing and their association with adverse outcomes.Materials and methodsHospital admission records from 2004 to 2020 with a primary discharge diagnosis of AECOPD were retrieved from Beijing Public Health Information Centre database. The anxiety and depression were identified from discharge diagnoses of each record. Joinpoint regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“… 5 COPD patients with anxiety often experience more frequent exacerbations that lead to longer hospital stays, higher medical costs, higher risks of readmission for acute exacerbation of COPD (AECOPD), and even higher mortality. 6–10 It has been reported that the prevalence of anxiety among inpatients with COPD is 10%–55%, and this is 13%–46% among outpatients, 11 although this might be underestimated, including in China. 8 …”
Section: Introductionmentioning
confidence: 99%
“… 5 COPD patients with anxiety often experience more frequent exacerbations that lead to longer hospital stays, higher medical costs, higher risks of readmission for acute exacerbation of COPD (AECOPD), and even higher mortality. 6–10 It has been reported that the prevalence of anxiety among inpatients with COPD is 10%–55%, and this is 13%–46% among outpatients, 11 although this might be underestimated, including in China. 8 …”
Section: Introductionmentioning
confidence: 99%